Pengaruh Budaya Sekolah Terhadap Karakter Disiplin Peserta Didik Kelas VIII di SMP Negeri 1 Ngunut Tulungagung - Ninda Halimatus Sa’diyah; Ikfi Khoulita (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This research is based on the problem of students' disciplinary character which is influenced by school culture at SMP 1 Negeri Ngunut Tulungagung. The emergence of problems with undisciplined behavior include coming to school not on time, skipping school, submitting assignments not on time, etc. The occurrence of undisciplined behavior at school shows that there has been a problem in terms of disciplinary character education. One way to improve school culture is by evaluating the school culture that has been implemented, so that the school knows where the school culture is lacking. Knowing the influence of school culture on the disciplinary character of class VIII students at SMP Negeri 1 Ngunut Tulungagung. This research uses quantitative research with a correlational type of research. The population of this research is 393 class VIII students at SMP Negeri 1 Ngunut. This research took samples using probability sampling techniques. In this study, researchers took a sample of 162 students based on criteria. Data collection was carried out using a questionnaire instrument. The data analysis technique uses requirements testing and hypothesis testing. The research results show that the results of the hypothesis test show that the results obtained are sig. amounting to 0.000 (0.000 < 0.05) so it is said that there is a positive and significant influence between the influence of school culture on the disciplinary character of students. The correlation coefficient test result (R) is 0.469, indicating that the two variables have a moderate relationship. Meanwhile, the coefficient of determination (R Square) value was obtained at 22%, while 78% was influenced by other factors not studied.